Comparison of warrant pricing models - Karpišová, Iveta; Witzany, Jiří, 1966-; Kravtsov, Oleg; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
The theme of this master’s thesis is warrant pricing methods. Four models will be presented, the benchmark Black-Scholes model originally developed for option pricing, the diluted version, the Galai-Schneller model and the Ukhov model implementing the firm volatility. Fourteen warrants quoted on the Hong Kong Stock Exchange are priced in the practical part. Appropriate risk-free rate and volatility measures are discussed. In the empirical part of the work results of the pricing models are presented. Author used three volatility estimation methods, the standard equal weighted, GARCH and implied volatility. The best results were given by the combination of the Galai-Schneller model and the implied volatility. The Black-Scholes model intended for option valuation performed the worst.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses